Integrated Pest Management for Mosquito Reduction around Homes and Neighborhoods - C. Roxanne Rutledge Connelly; Elizabeth Bolles; D. Culbert; James DeValerio; Michael Donahoe; K. Gabel; R. Jordi; J. McLaughlin; Anita Neal; Sally Scalera; E. Toro; Joseph Walter (EDIS)
This 40-page publication describes how homeowners can use an integrated pest management (IPM) program to help decrease pesticide use, reduce the risk of contracting mosquito-borne diseases, and ease the financial burden on local governments responsible for area-wide control. Modern mosquito control emphasizes source reduction to eliminate areas where mosquitoes thrive; surveillance to determine whether pesticide applications are necessary; screening; sanitation; and other techniques described in this document. The methods recommended in this publication are particularly effective in reducing mosquitoes that transmit diseases. Homeowners who take responsibility for identifying and eliminating sources of mosquito production around their homes and neighborhoods will improve health and quality of life for all Florida residents. Written by C. R. Connelly, E. Bolles, D. Culbert, J. DeValerio, M. Donahoe, K. Gabel, R. Jordi, J. McLaughlin, A. S. Neal, S. Scalera, E. Toro, and J. Walter, and published by the UF Department of Entomology and Nematology, September 2014.